An Optimally Designed Engineering Exosome–Reductive COF Integrated Nanoagent for Synergistically Enhanced Diabetic Fester Wound Healing. Issue 26 (31st May 2022) - Sun, Baohong; Wu, Fan; Wang, Xinye; Song, Qiuxian; Ye, Ziqiu; Mohammadniaei, Mohsen; Zhang, Ming; Chu, Xiaohong; Xi, Sheng; Zhou, Ninglin; Wang, Wentao; Yao, Cheng; et al.
Abstract: Oxidative stress and local overactive inflammation have been considered major obstacles in diabetic wound treatment. Although antiphlogistic tactics have been reported widely, they are also challenged by pathogen contamination and compromised angiogenesis. Herein, a versatile integrated nanoagent based on 2D reductive covalent organic frameworks coated with antibacterial immuno‐engineered exosome (PCOF@E‐Exo) is reported to achieve efficient and comprehensive combination therapy for diabetic wounds. The E‐Exo is collected from TNF‐α‐treated mesenchymal stem cells (MSCs) under hypoxia and encapsulated cationic antimicrobial carbon dots (CDs). This integrated nanoagent not only significantly scavenges reactive oxygen species and induces anti‐inflammatory M2 macrophage polarization, but also stabilizes hypoxia‐inducible factor‐1α (HIF‐1α). More importantly, the PCOF@E‐Exo exhibits intriguing bactericide capabilities toward Gram‐negative, Gram‐positive, and drug‐resistant bacteria, showing favorable intracellular bacterial destruction and biofilm permeation. In vivo results demonstrate that the synergetic impact of suppressing oxidative injury and tissue inflammation, promoting angiogenesis and eradicating bacterial infection, could significantly accelerate the infected diabetic fester wound healing with better therapeutic benefits than monotherapy or individual antibiotics. The proposed strategy can inspire further research to design more delicate platforms using the combination of immunotherapy with other therapeutic methods for more efficient ulcerated diabetic wounds treatments. Abstract : A versatile integrated nanoagent based on 2D reductive covalent organic frameworks coated with antibacterial immuno‐engineered exosome (PCOF@E‐Exo) is synthesized, and its first application in accelerating infected diabetic fester wounds healing is also reported. PCOF@E‐Exo is capable of suppressing oxidative injury and tissue inflammation, promoting angiogenesis, and eradicating bacterial infection for comprehensive combination therapy.